On a quest to maximize student learning potential - Pollard, Cheryl; McKendrick-Calder, Lisa; Bowman, Catherine; Heuver, Tanya (My University, 2017)
As educators, we are in search of ways to better assist students in their journey as they learn how to apply theoretical knowledge to practice based situations. Quest based learning is a unique methodology that extends student learning and engagement with course material beyond the classroom allowing them to solve problems and develop their critical thinking abilities. In our course students complete quests in preparation for class which increases their accountability and engagement with the content. This session will highlight current evidence based practices for quest based learning. Ways to create a learning community with student centered activities and active engagement will be explored. Strategies for developing and facilitating quest based learning will be discussed. Session participants will have the opportunity to participate in quest based learning activities and engage with an online learning platform.
Presented on March 6, 2017 at the Centre for the Advancement of Faculty Excellence - CAFÉ, MacEwan University in Edmonton, Alberta.
Keywords: quest based learning; student engagement